MATH SOLVE

4 months ago

Q:
# Drag the system of equation to the point that represents the solution to the system.ITEMBANK: Move to Bottom2x - y = -13y = x + 93x + 2y = 106x - y = 104x - 3y = 53x + 2y = -9x + y = 7x - y = -1y = 3x - 7y = 2x - 5y = 6x = -5

Accepted Solution

A:

using a graph tool

case 1)

Β 2x-y=-13

y=x+9

the solution is the point (-4,5)

see the attached figure N 1

case 2)

y=3x-7

y=2x-5

the solution is the point (2,-1)

see the attached figure N 2

case 3)

3x+2y=10

6x-y=10

the solution is the point (2,2)

see the attached figure N 3

case 4)

y=6

x=-5

the solution is the point (-5,6)

see the attached figure N 4

case 5)

4x-3y=5

3x+2y=-9

the solution is the point (-1,-3)

see the attached figure N 5

case 6)

x+y=7

x-y=-1

the solution is the point (3,4)

see the attached figure N 6

the total answer in the attached figure

case 1)

Β 2x-y=-13

y=x+9

the solution is the point (-4,5)

see the attached figure N 1

case 2)

y=3x-7

y=2x-5

the solution is the point (2,-1)

see the attached figure N 2

case 3)

3x+2y=10

6x-y=10

the solution is the point (2,2)

see the attached figure N 3

case 4)

y=6

x=-5

the solution is the point (-5,6)

see the attached figure N 4

case 5)

4x-3y=5

3x+2y=-9

the solution is the point (-1,-3)

see the attached figure N 5

case 6)

x+y=7

x-y=-1

the solution is the point (3,4)

see the attached figure N 6

the total answer in the attached figure